Renal function estimation in critically ill newborns in Erbil. - Hameed Abdul Xafur; Lana Ahmed Mohammed (Advanced Medical Journal)
Background and objectives: Acute kidney injury is a common in critically ill neonates all over the world, characterized by an acute decline in renal function, the result of which ranges from minimal alteration in serum creatinine to an a uric renal failure our objective is to estimate renal function and aetiologies of renal function deteriorated in critically ill neonates.